NILAI-NILAI FILSAFAT KETUHANAN DALAM TEKS Ä€DIPARWA - Wulandari, Ni Putu Ayu Desi; Untara, I Made Gami Sandi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Ä€diparwa is the initial part of the aá¹£á¹adaÅ›aparwa which forms the MahÄbhÄrata which tells various stories which breathe Hindu teachings. Besides containing very high educational values that can be used as a mirror in daily life, the Ä€diparwa text also contains the value of the Philosophy of God. The values of the Divine Philosophy in the Ä€diparwa Text consist of pantheism, totemism, the oneness of God, and Ätma. Pantheism was discovered when RÄma ParaÅ›u gave seeds to the empresses so that in the world there would be a ká¹£atriya again and about the incarnation of the gods into the world to eradicate the incarnation of the giants. Totemism is shown at the birth of the Garuá¸a and concerning the 3 (three) dragons, namely Anantabhoga, BÄsuki, and Taká¹£aka. The mention of many deities is found in the text of ipdiparwa, even though God remains single.